(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article is devoted to the study of gender features and differences in the behavior of boys and girls. The goal of the work is to systematize and analyze the behavior of children in situations of official and unofficial intergender communication. Through communication, the child learns the world and himself in it, acquires social experience, develops and establishes himself as a person. The most characteristic feature of communication is the disclosure of the subjective world of one person for another. This activity is extremely important for a child, who begins to discover a complex and diverse world. The article presents the results of a sociometric study aimed at studying the intergenerational communication of junior pupils.